The Role of Natural Killer Cells in Multiple Sclerosis and Their Therapeutic Implications - Chanvillard, Coralie; Jacolik, Raymond F.; Infante Duarte, Carmen; Nayak, Ramesh C. (Frontiers in Immunology, 2013)
Multiple sclerosis (MS) is assumed to be an autoimmune disease initiated by autoreactive T cells that recognize central nervous system antigens. Although adaptive immunity is clearly involved in MS pathogenesis, innate immunity increasingly appears to be implicated in the disease. We and others have presented evidence that natural killer (NK) cells may be involved in immunoregulation in MS, leading to the question of whether a particular NK cell subtype will account for this effect. Changes of NK cell functionality in MS were associated with MS activity, and depletion of NK cells exacerbated the course of disease in a murine model of MS, experimental autoimmune encephalomyelitis. Several studies described a deficiency and transient “valleys” in NK cell killing activity in human MS, which may coincide with symptomatic relapse. However, the molecular basis of the defect in killing activity has not been determined. We discuss results on the expression of perforin in CD16+ NK cells and the existence of an inverse relationship between myelin loaded phagocytes and the proportion of CD16+ NK cells expressing perforin in the circulation. This inverse relationship is consistent with a role for NK cell killing activity in dampening autoimmunity. On the other hand, it has been broadly reported that first line MS therapies, such as interferon-beta, glatiramer acetate as well as escalation therapies such as fingolimod, daclizumab or mitoxantrone seem to affect NK cell functionality and phenotype in vivo. Therefore, in this review we consider evidence for the immunoregulatory role of NK cells in MS and its animal models. Furthermore, we discuss the effect of MS treatments on NK cell activity.